2020
DOI: 10.1136/postgradmedj-2019-136959
|View full text |Cite
|
Sign up to set email alerts
|

Stroke and osteoporosis: a Taiwan cohort study

Abstract: BackgroundOsteoporosis and stroke are major health problems that have potentially overlapping pathophysiological mechanisms. The aim of this study was to estimate osteoporosis risk in Taiwan patientswho had a stroke.MethodThis study retrieved data contained in the Taiwan National Health Insurance Research Database for a population-based sample of consecutive patients either hospitalised for stroke or treated for stroke on an outpatient basis. A total of 7550 newly diagnosed patientswho had a stroke were enroll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 32 publications
2
5
0
Order By: Relevance
“…Third, according to recent researches [39], cerebrovascular disease generally considered to be associated with osteoporosis. Zhang et al [40] investigated database for Taiwan population, they concluded that the population of patients with stroke revealed a higher osteoporosis risk, and poststroke osteoporosis was signi cant in male gender, which is also consistent to our study. Previous study [41] used osteoporosis related factors to predict risk of fracture in Chinese male population.…”
Section: Discussionsupporting
confidence: 92%
“…Third, according to recent researches [39], cerebrovascular disease generally considered to be associated with osteoporosis. Zhang et al [40] investigated database for Taiwan population, they concluded that the population of patients with stroke revealed a higher osteoporosis risk, and poststroke osteoporosis was signi cant in male gender, which is also consistent to our study. Previous study [41] used osteoporosis related factors to predict risk of fracture in Chinese male population.…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, even though stroke is a well-known risk factor for developing osteoporosis ( 31 , 32 ), the utilization rates of BMD testing and osteoporosis treatment were quite low after stroke. The likelihood of using these two measures was even lower in patients with greater stroke severity.…”
Section: Discussionmentioning
confidence: 99%
“…This study further demonstrated that stroke patients carried a significantly higher risk of low-trauma fracture within one year than non-stroke patients (1.7% vs. 0.6%, p <0.001). In particular, stroke may contribute more to the risk of subsequent osteoporosis in the male sex and younger age ( 31 ). A decline in cognitive function and a high comorbidity burden such as dementia also increase the risk of osteoporotic fractures among stroke survivors ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…The age, gender and average insured payroll of the LHID2010 and NHIRD are not significantly different. The LHID2010 has been used for stroke-related studies 20–23…”
Section: Methodsmentioning
confidence: 99%